Rape by the numbers : producing and contesting scientific knowledge about sexual violence - Levine, Ethan Czuy (Critical issues in crime and society, 2021)
Science plays a substantial, though under-acknowledged, role in shaping popular understandings of rape. Statistical figures like "1 in 4 women have experienced completed or attempted rape" are central for raising awareness. Yet such scientific facts often become points of controversy, particularly as conservative scholars and public figures attempt to discredit feminist activists. Rape by the Numbers explores scientists' approaches to studying rape over more than forty years in the United States and Canada. In addition to investigating how scientists come to know the scope, causes, and consequences of rape, this book delves into the politics of rape research. Scholars who study rape often face a range of social pressures and resource constraints, including some that are unique to feminized and politicized fields of inquiry. Collectively, these matters have far-reaching consequences. Scientific projects may determine who counts as a potential victim/survivor or aggressor in a range of contexts, shaping research agendas as well as state policy, anti-violence programming and services, and public perceptions. Social processes within the study of rape determine which knowledges count as credible science, and thus who may count as an expert in academic and public contexts.